Pembekalan Keterampilan Membatik oleh Batik “Seng” bagi Kelompok Marginal Desa Sengguruh Kabupaten Malang - Aris Siswati; Boge Triatmanto; Anwar Sanusi (STIE Malangkucecwara, 2021)
National economic development can be realized, one of which is economic independence by encouraging the number of entrepreneurs, increasing business activities in the form of businesses and businesses on a small, medium or large scale. One of the potentials to become independent entrepreneurs is young people who of course must first have the provision of education. The reality is that there are still school-age teenagers who do not have the opportunity to get the right to education due to several things, one of which is economic limitations that prevent them from continuing their education. The consequences that arise from situations that are not good, namely teenagers who cannot continue their schooling will cause a new problem for both the child himself and his environment. The form of community service activities carried out is holding written batik training activities targeting marginal groups in Sengguruh Village, Malang Regency with a total of 30 participants. The purpose of this activity is to provide training participants with the opportunity to develop themselves and get alternative business ideas. The results obtained from this activity are an increase in insight and skills in making batik, increasing motivation for training participants to develop themselves, participants getting alternative business ideas that can be chosen as professions that have the potential to generate income and obtain business network information